Skill acquisition (TVET) and employment in Sarawak - Ohagwu, Onyekachi; Nwanesi, Peter Karubi; Poline, Bala (John Wiley & Sons Ltd, 2022)
This paper examines the role of technical and vocational education and training (TVET) as a booster of employment opportunities in Sarawak, highlighting the importance of TVET as a catalyst that promotes individuals’ chances to gain employment, with the ultimate goal of improving their socioeconomic living conditions and overall development. As a case study focusing on Tabung Ekonomi Gagasan Sarawak (TEGAS) TVET programmes and applying the qualitative research methodological approach, this paper gathered and analysed raw data from research participants and concluded that (1) TVET plays significant roles in facilitating individuals’ or groups’ employment chances, especially within tech-based industries, and (2) employments are rewarded with remunerations and thus facilitate individuals' socio-economic developments.